PENGARUH KOMPETENSI PEDAGOGIK DAN KECERDASAN SPIRITUAL TERHADAP KINERJA GURU DI MADRASAH TSANAWIYAH NEGERI SE-KOTA PEKANBARU - Rahmah, Ismiyatul (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2021)
Abstrak: This research was instigated by the low of teacher performance problem.  It could be seen from indications happening—there were teachers who were late to come to school, so they were late to do the learning activities, there were teachers who did not show their creativity in developing learning material actively, the lesson plan made by them used monotonous media, there were teachers who were lack of various and newest methods directing to student activeness, the teachers tended to use the old methods such as lecturing, discussing, and taking notes, there were teachers who were not yet able to manage  the classneatly and comfortably, and there were teachers who let the chairs scattered when they wanted to begin the learning activity.  Those phenomena showed the teacher performance that was not yet maximum and still on low category.  This research aimed at knowing the influence of pedagogical competence and spiritual quotient toward teacher performance at Islamic Junior High Schools in Pekanbaru.  Descriptive statistical and inferential analysis techniques were used in this research to obtain the data.  All teachers ofIslamic Junior High Schools in Pekanbaru were the population of this research, there were 3State Islamic Junior High Schools in Pekanbaru and 165 teachers.  Total sampling technique was used in this research, and 35 Islamic Education subject teachers were selected.  Based on the research findings, 1) there was aninfluence of pedagogical competence toward teacher performance at Islamic Junior High Schools in Pekanbaru, it meant that the higher pedagogical competence was, the higher teacher performance would be in doing their tasks; 2) there was aninfluence ofspiritual quotient toward teacher performance at Islamic Junior High Schools in Pekanbaru, it meant that the higher spiritual quotient was, the higher teacher performance would be in doing their tasks and responsibilities at the school; and 3) there was aninfluence of pedagogical competence and spiritual quotient toward teacher performance at Islamic Junior High Schools in Pekanbaru.  Pedagogical competence and spiritual quotient in real determined and contributed to the better teacher performance.  The influence of both variablespedagogical competence and spiritual quotient toward teacher performance was 31.5%, and the rest 68.5% was not discussed in this research.